Student Online Shopping Behaviour Through Instagram - Davala, Muhammad Riyan; Amanda, Luthfia Salma; Syafitri, Fadiyah Nur Azizah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
The rise of consumption through online shops by students is one of the background problems in this study. Generally, students do shop online not based on mere needs, but for the sake of pleasure and lifestyle that causes a person to become wasteful or better known as consumptive behavior or consumerist behavior. This research focused on the pattern of shopping behavior through Instagram among female students. This study uses qualitative research methods involving 50 respondents in the scope of undergraduate students of several universities in Indonesia. In this study, it was described that the behavior of shopping through instagram among students was shown by the intensity of their spending which was counted a lot, with an average allowance of mostly Rp. 1,000,000 - Rp. 5,000,000 once a month there were those who spent more than 6 minutes until more than 20 minutes one time visited instagram. They are trying to find recommendation and information by using more in instastory feature in instagram. They almost influencing by their friend and public figure. In conclusion instagram really give impact in their behavior in online shopping.